HISTORY OF THE DEVELOPMENT OF SPORTS IN UZBEKISTAN - Utemuratova Dinara Nurillaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This research delves into the historical and contemporary development of sports in Uzbekistan, tracing its evolution from traditional cultural practices to modern international achievements. The study explores how sports like Kurash, football, boxing, judo, and gymnastics have shaped and been shaped by the country’s social and political landscapes. It highlights the Soviet legacy, the role of sports in fostering national identity post-independence, and the influence of globalization on athlete development and sports infrastructure. The research also examines Uzbekistan’s successes in international competitions, particularly the Olympics, and discusses the challenges and opportunities for further growth in the sports sector.